2018
DOI: 10.1186/s12939-018-0815-z
|View full text |Cite
|
Sign up to set email alerts
|

Widening inequalities in multimorbidity? Time trends among the working population between 2005 and 2015 based on German health insurance data

Abstract: BackgroundPrevious research has produced evidence for social inequalities in multimorbidity, but little is known on how these disparities change over time. Our study investigates the development of social inequalities in multimorbidity among the middle-aged and older working population. Special attention is paid to whether differing time trends between socio-economic status (SES) groups have taken place, increasing or decreasing inequalities in multimorbidity.MethodsThe analyses are based on claims data of a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…These in-depth analyses contribute to the global research on multimorbidity,1 , 59 and identify distinct ‘types’ of multimorbidity in specific age groups of patients, and support the need for care delivery that accounts for the evolution of multimorbidity over time 60 –. 63 While beyond the scope of the current research, the findings reported in this article could be used to re-examine the potential for effective case management through a more tailored approach to multimorbidity and a more integrated set of health services.…”
Section: Discussionmentioning
confidence: 80%
“…These in-depth analyses contribute to the global research on multimorbidity,1 , 59 and identify distinct ‘types’ of multimorbidity in specific age groups of patients, and support the need for care delivery that accounts for the evolution of multimorbidity over time 60 –. 63 While beyond the scope of the current research, the findings reported in this article could be used to re-examine the potential for effective case management through a more tailored approach to multimorbidity and a more integrated set of health services.…”
Section: Discussionmentioning
confidence: 80%
“…The variable of occupation type was defined based on an occupation classification system developed by Blossfeld [19]. In the present study, following Tezlaff et al [10], the original 12 groups were re-categorized into four groups: highly qualified, specialist, skilled, and unskilled.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of multimorbidity ranged from 3.0% to 30.0% [3]. Tezlaff and colleagues [10], for example, reported the prevalence rate was about 3.0 among the the working German population. The rate was lower than that obtained in a Canadian sample aged 45–49 (about 30.0%) [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations